Chest Wall Syndrome - Isti Mardiana Soetartio; Agus Dwi Susanto; Dicky Soehardiman; Budhi Antariksa (Respiratory Science, 2021)
Chest wall syndrome is the most frequent cause of chest pain complained by patients admitted to the physician’s office, in outward as well as in emergency department. It may affect all ages with sex ratio of 1:1 between man and woman. History of illness and sensibility to palpation or tenderness were the keys to the diagnostic approach. Pain was generally moderate, well localized, continuous or intermittent over a number of hours to days or weeks and was amplified by position or movement that was commonly located on the left side of the chest. Chest wall syndrome is usually a common and benign condition, but it leads to anxiety and frequent recurrence. Definitive treatment is not yet confirmed and treatment for the different condition causing isolated musculoskeletal chest pain is poor. Therefore, some options to avoid aggravating physical activities, stretching, and simple analgesics as needed are the best choices of current management.